Education and race from Empire to Brexit - Tomlinson, Sally (Policy Press, 2019)
This book offers an historically informed discussion of the failure of the education systems in Britain to counter hostilities towards racial and ethnic minorities and migrants, which have escalated after the vote to leave the European Union, and left schools and universities failing to engage with a multiracial- multicultural society.